SOCIAL DETERMINANTS OF ANTENATAL CARE AND LABOUR OF PREGNANT WOMAN IN PRIMARY CARE CENTERS DURING THE COVID-19 PANDEMIC IN BLITAR CITY - Devy, Shrimarti Rukmini; Ernawaty, Ernawaty; Sulistyorini, Yuly (Universitas Airlangga, 2025)
The COVID-19 pandemic has impacted pregnant women's access to health services, including antenatal care (ANC) visits and the choice of delivery place. This study aims to analyse the factors influencing pregnant women's behavior regarding ANC visits and delivery place selection in Blitar City during the pandemic. This research employed a quantitative method with a cross-sectional design. Data were collected using questionnaires administered to pregnant women in Blitar City who met the inclusion criteria. Data analysis involved statistical tests to identify the relationships between independent variables (maternal knowledge, maternal attitudes, perceptions of healthcare workers, family perceptions, and information availability) and dependent variables (ANC visit behaviour and delivery place selection). The results showed that maternal knowledge and perceptions of healthcare workers significantly influenced ANC visit behaviour, whereas maternal attitudes, family perceptions, and information availability did not show significant effects. Conversely, in delivery place selection behaviour, maternal attitudes, family perceptions, and information availability were significant factors, while maternal knowledge and healthcare workers' perceptions were not. It is concluded that individual and social factors play important roles in determining pregnant women's behaviour during a health crisis. Interventions aimed at improving health education, family support, and access to accurate information are essential to strengthen maternal health services during the pandemic.